Fundamental of FAA AD 2025-04-03 Implementation on The Boeing 737-800 NG Turbine Exhaust System - Ani Widuri; Sovian Aritonang; Gita Amperiawan; Andy Putranto; Lalu Akbar; Muhammad Zainal Furqon (CV. Rayyan Dwi Bharata, 2025)
The turbine exhaust system is a critical component in maintaining the structural integrity and airworthiness of turbofan-powered transport aircraft on CFM56-7B engines, the Federal Aviation Administration (FAA) issued Airworthiness Directive (AD) 2025-04-03, requiring the modification of the engine primary exhaust nozzle to prevent potential separation and structural damage to the fuselage. This study evaluates the implementation of the directive in the Sriwijaya Air fleet under the scope of Boeing Special Attention Requirements Bulletin 737-78-1106 RB Revision 1. The research method combines airworthiness compliance analysis, engineering inspection, and procedural verification using the Accomplishment Instructions defined in EO M-78-003. The modification involved the installation of TOP KIT 002A0123-1 for Off-Wing Rework Kit and 002A0123-2 for On-Wing Installation Kit, the replacement of affected part numbers 314A2610-1, -62, -68, and incorporation of Airworthiness Limitations (AWLs) Nos. 2, 3, and 4 into the operator’s maintenance program. The results confirm that the affected aircraft—registrations PK-CRI, PK-CRA, PK-CRE, and PK-CRH—belong to Group 1 configuration and require mandatory action within 90 days after the AD effective date April 8, 2025, and must be inspection completed before July 31, 2028.